Procalcitonin is One of the Predictive Factors of Dehiscence of the Colorectal Anastomosis - Djeri, Jugoslav; Ćulum, Jovan; Aleksić, Zoran; Šaran, Dalibor; Rajić, Romana (Scripta Medica, 2022)
Background/Aim: Dehiscence of the colorectal anastomosis is one of the most serious complications in digestive surgery that is still present in a large percentage today, which significantly increases the cost of treatment and can lead to death. Due to all the above, early detection of anastomotic dehiscence is veryimportant, as well as the decision on surgical treatment. Procalcitonin (PCT) is thought to be an important marker of inflammation and sepsis. Aim of this paper was to confirm PCT as a marker of great sensitivity in early diagnosis of anastomotic leakage.Methods: The study included patients who underwent surgery for colorectal cancer in the period from 2016 to 2020. Patients were operated according to an elective protocol and with an open surgical approach. In patients, PCT values were measured on the 2nd and 4th postoperative day (POD) to determine theassociation between elevated PCT values and the onset of dehiscence of the colorectal anastomosis.Results: A study was conducted in 118 patients in whom a stapler colorectal anastomosis was created. Colorectal anastomosis dehiscence occurred in 10 patients. In 4 patients with dehiscence, no re-surgical intervention was required, but they were taken care of by conservative methods. Repeated surgery was performed in 6 patients. In all patients with dehiscence, there was a multiple increase in the value of PCT above normal.Conclusion: PCT has high sensitivity and specificity (85 and 74 %, respectively) as a marker in dehiscence of colorectal anastomosis. In this study it was found that PCT values were significantly correlated with the dehiscence of anastomosis 2nd POD and especially 4th POD.
Keywords: Colorectal anastomosis; Anastomotic dehiscence; Procalcitonin